In vitro diagnostic accuracy of low‐dose CBCT for evaluation of peri‐implant bone lesions - Schwindling, Franz Sebastian; Hilgenfeld, Tim; Kronsteiner, Dorothea; Rammelsberg, Peter (Clinical oral implants research, 2019)
Objectives - To investigate the in vitro diagnostic accuracy of low‐dose cone‐beam computed tomography (LD‐CBCT) for the detection, classification, and measurement of peri‐implant bone lesions.
[Correction added on 11 November, after first online publication: Projekt Deal funding statement has been added.] The copyright line for this article was changed on 11 November 2020 after original online publication
Gesehen am 20.01.2021